Evaluation of Microbiological Quality of Commercially Available Bottled Water in the City of Dhaka, Bangladesh (Stamford Journal of Microbiology, 2011)
Bottled water has become one of the most popular drinks in Bangladesh. Now a days it is easily available in the market. Due to lack of confidence on municipal supply water, people now prefer to drink bottled water instead of tap water, mostly when they are outside the home, and in many occasions. In the present study, the presence of total coliforms (TC) and fecal coliforms (FC) from nine commercially available lacal Bangladeshi bottled water samples were examined. The obtained results indicated that most of the studied bottled water were out of their safety guidelines and hence some chronic diseases (renal failure, liver cirrhosis and anemia) are expected in the area understudy, because 68.89% and 31.11% of the bottled water sampled in the current study showed heterotrophic plate counts (HPC) within a range of 1-500 (cfu/ml) and greater than 500 (cfu/ml), respectively and 0% samples showed less than 1 (cfu/ml) in heterotrophic plate counts. The results also revealed the ill performance and poor drinking water quality of the purification systems of the investigated water samples. 28% of the respondents considered that the quality of bottled water was satisfactory, in contrast to the 26% of the respondent, who judged that the quality of bottled water was not that satisfactory. However, the highest (34%) number of the respondents did not know whether the quality of the bottled water is good or not satisfactory. Recommendation was suggested for new treatment systems of the investigated suspicious water to prevent human illness.  DOI: http://dx.doi.org/10.3329/sjm.v1i1.9099Stamford Journal of Microbiology, Vol.1(1), July 2011, p.24-30